Rectal resection for Schnitzler’s metastasis in a patient presenting with severe rectal stenosis: case report and review of the literature - Doğan, Semra; Demirbaş, Sezai; Samadov, Elgun; Öziş, Salih Erpulat; Uslu, Hatim Yahya (The European Research Journal, 2019)
Rectal metastasis resulting from the hematogenous spread of gastric cancer (Schnitzler’s disease) is rarely seen. We report a case of 53-year-old female with rectal metastasis from gastic cancer who presented with abdominal pain, tenesmus, and severe constipation. Digital rectal examination revealed a severe stenosis 5-6 cm from the dentate line. Sigmoidoscopy showed a narrowed lumen at 5 cm up from the dentate line. The evident radiologic finding was circumferential stenosis of the rectum located at the same level. Very low anterior resection and total mesorectal excision with coloanal anastomosis in addition to protective ileostomy were performed. Pathological examination revealed metastatic adenocarcinoma (Schnitzler’s metastasis). The patient was discharged on the 9th postoperative day with no adverse events. It should be kept in mind that rectal stenosis could be metastasis from gastric carcinoma if consistent with the patient’s history.